Community Advisory Boards in Community-Based Participatory Research: A Synthesis of Best Processes - Susan D. Newman, PhD, RN, CRRN; Jeannette O. Andrews, PhD, APRN-BC, FNP; Gayenell S. Magwood, PhD, RN; Carolyn Jenkins, DrPH, APRN, BC-ADM, RD, LD, FAAN; Melissa J. Cox, MPH; Deborah C. Williamson, DHA, MSN, CNM (Centers for Disease Control and Prevention, 2011)
Community-based participatory research (CBPR) is a paradigm to study and reduce disparities in health outcomes related to chronic disease. Community advisory boards (CABs) commonly formalize the academic-community partnerships that guide CBPR by providing a mechanism for community members to have representation in research activities. Researchers and funding agencies increasingly recognize the value of the community's contribution to research and acknowledge that community advisory boards are a key component of successful CBPR projects. In this article, we describe the best processes for forming, operating, and maintaining CABs for CBPR. We synthesize the literature and offer our professional experiences to guide formation, operation, and maintenance of CABs.